2014
DOI: 10.15835/nbha4229573
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Nutraceutical Components of Commercial Eggplant Types Grown in Sinaloa, Mexico

Abstract: The nutrimental composition and main nutraceutical components were determined in Chinese, Philippine, American, Hindu and Thai eggplant (Solanum melongena L.) types grown in Sinaloa, Mexico. Thai type showed the highest amount of protein (0.90%), crude (1.54%) and dietary (3.93%) fibre and the highest concentrations of total soluble phenolics (2049 mgCAE 100g-1) and chlorogenic acid (1700 mg 100g-1). Hindu type obtained the highest content of the minerals potassium (191.19 mg 100g-1), calcium (59.63 mg 100g-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 44 publications
4
7
0
Order By: Relevance
“…The range of carbohydrate content was from 4.27% to 6.63% (Table 2) The maximum content was observed in BARI Begun-6 (6.63%), Hybrid 5x216 (6.27%) and SM233 (6.05%). These results were similar to those obtained by Nino-Medina et al (2014), where they obtained a carbohydrate content ranging from 5.96% to 7.92% in different eggplant types. In our study we observed several low carbohydrate contents in eggplant cultivars which were less than 5% viz., BARI Begun-8 (4.27%), BARI Hybrid Begun-4 (4.61%), BARI Begun-4 (4.73%), Hybrid 21x11 (4.91%) and BARI Begun-10 (4.94%).…”
Section: Carbohydrate *supporting
confidence: 90%
See 3 more Smart Citations
“…The range of carbohydrate content was from 4.27% to 6.63% (Table 2) The maximum content was observed in BARI Begun-6 (6.63%), Hybrid 5x216 (6.27%) and SM233 (6.05%). These results were similar to those obtained by Nino-Medina et al (2014), where they obtained a carbohydrate content ranging from 5.96% to 7.92% in different eggplant types. In our study we observed several low carbohydrate contents in eggplant cultivars which were less than 5% viz., BARI Begun-8 (4.27%), BARI Hybrid Begun-4 (4.61%), BARI Begun-4 (4.73%), Hybrid 21x11 (4.91%) and BARI Begun-10 (4.94%).…”
Section: Carbohydrate *supporting
confidence: 90%
“…Na content varied largely in our study with a range from 4.06 to 8.51 mg 100g -1 . It was similar to the findings of Nino-Medina et al (2014), where the concentration was 5.61 to 11.54 mg 100g -1 . Ekholm et al (2007) found a similar pattern and mineral content in eggplants cultivated in Finland, as compared to our work, where K displayed the highest concentration (175 mg 100g -1 ) and Cu displayed the lowest concentration (0.03 mg 100g-1).…”
Section: Ascorbic Acid (Vitamin C)supporting
confidence: 90%
See 2 more Smart Citations
“…Total phenolic content of eggplant samples from the greenhouse conventionally heated and with IR ranged from 941.63 to 1493.91 mg GAE/100 g DW and from 1109.78 to 1330.56 mg GAE/100 g DW, respectively. The TPC results of the studied eggplant samples were similar to those that were reported by Hanson et al [17], for 35 eggplant species from different origins (740-1430 mg of chlorogenic acid equivalents /100 g DW), higher than those that were reported by Raigón et al [18], for 31 eggplant cultivars (562-965 mg of chlorogenic acid equivalents /100 g DW) and lower than those that were reported by Niño-Medina et al [19], for five commercial eggplant types from Mexico (1350-2049 mg of gallic acid equivalents per 100 g DW). It is important to mention that many factors may affect TPC, such as the harvesting season, the temperature, the intensity and type of light, the eggplant species, the eggplant type (wild or cultivated), the eggplant size, agronomic and genetic factors, etc.…”
Section: Total Phenolic Content (Tpc) Antiradical and Antioxidant Actsupporting
confidence: 89%